Pemberian Nutrisi AB Mix dan Pupuk Urea terhadap Pertumbuhan Tanaman Pakcoy (Brassica rapa L) pada Sistem Budidaya Hidroponik Vertikultur - Reza Efendi; Nurma Ani; Dermawan Hutagaol (Jurnal Agrofolium, 2026)
The purposelly this research was to established the impact towards of Ab Mix nutrition also urea fertilizer and interaction towardstwo fertilizers towards growth of pakcoy plants. This study was using Factorial Randomized Block Design within 2 factors study also3 replications, which is first aspect was ab mix nutrition (A) when incluing toward 3 levels, are A0 = Control, A1 = 4 ml liter-1 of water plot-1, A2 = 8 ml liter-1 of water plot-1. The second aspect using urea fertilizer (U) when including toward f 4 levels, are U0 = Control, U1 = 3.6 g liter-1 of water plot-1, U2 = 5.4 g liter-1 of water plot-1, U3 = 7.2 g liter-1 of water plot-1. The parameters observing are plant that height (cm), leaf length (cm), leaf width (cm), plant leaf area (cm2), pakcoy weight per sample (g) alsopakcoy weight per plot (g). The yields was shown that AB Mix nutrition significan impact toward plant height, leaf length, leaf width, leaf area, pak choy weight per sample, also pak choy weight per plot. Urea fertilizer established significant impact pak choy weight per sample also pak choy weight per plot, however has no significant impact towards plant height, leaf length, leaf width, also leaf area. The interaction among AB Mix nutrition and urea fertilizer has no significant impact towards whole oberseve parameters.